PENGELOLAAN RETRIBUSI PADA TERMINAL LIMBOTO KABUPATEN GORONTALO - Suprapto, SriSrihandayani (Program Studi Akuntansi, 2019)
The objective of research was to describe the retribution management in Limboto station, Gorontalo district. This research used descriptive approach whit qualitive method. The resuld showed in retribution management of the station not fully said to be maximal especially in the planning and supervision sector. This is cause by several things, namely the non-socislization of government ordinance, the society not involved in determining retribution rates, and there is ignorance of the station officer abou the toilet which the retribution collected by the third person. The effective sector is in implementation part which followed by the existing procedures with applicable laws